An Exploration of the Communication Styles of Women in Managerial Positions Based on the Feminine Communication Style in the Workplace - Claassen, Kayla (The IIE, 2020)
The purpose of this study was to understand how women in managerial positions approach communication styles based on the perceived undermining of the feminine communication style in the workplace (Mohindra & Azhar,2012). Women are evaluated more negatively in leadership roles in comparison to men, even if they display masculine leadership characteristics (Jackson, Alberti & Snipers, 2013). Based on these preconceived views women often take on a masculine approach to leadership, but studies have shown that it lowers competence and perceived effectiveness meaning that the use of the masculine communication approach sounds ideal, but when practice by women it is often less successful (Jackson et al., 2013). The researcher that conducted the study drew five females from a sample who fitted the profile of the sample that was needed. A once off in-depth WhatsApp video call interview was conducted to collect the data the researcher required by asking open-ended questions to ensure that all the necessary information was obtained and that there was a good understanding of the participants. The research findings stated that females have more negative experiences than positive with using both the masculine and feminine communication approach to leadership positions due to the stereotyped characteristics that accompany their gender. For this reason, and despite the undermining of the feminine communication approach, females still felt like the qualities of the feminine communication approach helped them get more out of people and continued to use it. The research showed that the core issue is a lack of studies conducted on the success of the feminine communication style, misunderstanding and misinterpreting of genders linguistic styles and the meaning behind it, as opposed to females not having the desired communication approach or being fit for leadership positions.
Keywords: Women; Communication styles; Managerial positions; Workplace communication; Feminine communication styles